THE EFFORT TO IMPROVE THE MATHEMATICS LEARNING RESULT THROUGH COOPERATIVE LEARNING MODEL OF LEARNING TOGETHER (LT) TYPE FOR SMP N 1 RAKIT - Gilang Wisnu Adi; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
The conventional method in learning mathematics made the students passive to comprehend especially for the students 8 grade of SMP N 1 Rakit District of Banjarnegara. The purpose of this research was to improve the mathematics learning result of students through learning together (LT) type from the cooperative learning model. This research was Class action research (CAR). The subjects of this study were the first semester of eighth-grade students of SMP Negeri 1 Rakit in the academic year of 2016/2017 about 30 students. The object of this study was a cooperative learning model of learning Learning Together (LT) type. The data were collected through observation, interview, and final test cycle. The analysis of the data was used by descriptive qualitative data analysis. The results showed that the learning of mathematics through while of cooperative learning model of learning together (LT) type can improve students' mathematics learning results. This can be seen from the improvement score. In the first cycle, Most of the students got 72 by the percentage of students completed amount to 56.667%. it increased in the second cycle to 81.884 score with the percentage of students completed an amount about 96.667%.